Caracterización del microcrédito en las instituciones financieras del Cantón Piñas - Chamba Condoy, Gissella Lisbeth (2024)
The purpose of this research was to analyse the characteristics of the microcredits granted by financial institutions in the Piñas canton, and to reveal the impact on the sector. To this end, a mixed methodology was used with a descriptive, correlational and exploratory scope. A survey was also used to collect information from the 12 financial institutions in the locality. Additionally, with the data obtained from the official websites, a correlation analysis was carried out using the Pearson method for the variables microcredit, poverty and unemployment. In addition, the information obtained was used to establish the characteristics of credit elements such as: amounts, terms, guarantees, interest rates, among others. It was also possible to determine the comparative level between institutions to determine those with the best microcredit practices. In conclusion, it was found that the Marcabelí Cooperative and the Espoir Foundation offer better opportunities for accessibility to the micro-enterprise sector by opening up to people with low credit history scores. In relation to interest rates, it is the public bank represented through BanEcuador that grants the lowest rates and is also the institution with the highest levels of microcredit portfolio. Finally, there is no evidence of a relationship between the microcredit portfolio and the alleviation of poverty and unemployment levels.